2008
DOI: 10.1002/ejoc.200800089
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine‐Catalyzed Asymmetric Synthesis of 2,2‐Disubstituted Chromane Skeletons by Intramolecular Oxa‐Michael Addition

Abstract: The guanidine-catalyzed 6-exo-trig-type intramolecular asymmetric oxa-Michael addition of α,β-unsaturated esters with a 2-hydroxyaryl moiety at the C-5 carbon has been examined for the construction of chromane skeletons with a quaternary carbon chiral center. The bulkiness of the alkyl group and the E/Z geometry of the α,β-unsaturated ester function played important roles in the asymmetric induction and (4S,5S)-2-[(R)-1-hydroxymethyl-2-phenylethylimino]-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…It is theoretically possible to introduce five chiral centers in the guanidine system. We found that modified guanidines prepared using our original methods [4][5][6] were effective not only in catalytic [7][8][9][10][11][12][13] but also in stoichiometric asymmetric syntheses. 14,15) The concept of modified guanidines as chiral auxiliaries in asymmetric synthesis is illustrated in Chart 2, [16][17][18] in which reactive, but resonance-stabilized, guanidinium salts 5 could be produced from guanidines 4 by quarternarization with a reagent (A-B).…”
Section: Modified Guanidines As Chiral Auxiliaries (Functionality As mentioning
confidence: 99%
“…It is theoretically possible to introduce five chiral centers in the guanidine system. We found that modified guanidines prepared using our original methods [4][5][6] were effective not only in catalytic [7][8][9][10][11][12][13] but also in stoichiometric asymmetric syntheses. 14,15) The concept of modified guanidines as chiral auxiliaries in asymmetric synthesis is illustrated in Chart 2, [16][17][18] in which reactive, but resonance-stabilized, guanidinium salts 5 could be produced from guanidines 4 by quarternarization with a reagent (A-B).…”
Section: Modified Guanidines As Chiral Auxiliaries (Functionality As mentioning
confidence: 99%
“…In addition, the current method could be applied to the AIOM addition of the ester congeners 25a-d to provide the corresponding dihydrobenzofurans 26a-d with higher enantioselectivities (86-89% ee) as compared to literature precedents [52][53][54][55][56]. It is worthy to note that the construction of a chiral tetrasubstituted carbon center was also successful, and the corresponding O-heterocycle 26d was obtained in 75% yield with 86% ee.…”
Section: The Intramolecular Oxa-michael Addition Of Phenolsmentioning
confidence: 90%
“…4 prevail in natural products and pharmaceuticals, the AIOM reaction of α,β-unsaturated amides and esters bearing phenolic OH groups would be useful and practical from the viewpoint of atom economy. So far, there have been only a few reports on the same reaction of α,β-unsaturated esters [52][53][54][55][56], and no reports with regard to α,β-unsaturated amides have yet been described. Recently we discovered that benzothiadiazine catalyst 3a effectively promoted the AIOM addition to α,β-unsaturated amides 23a-i (Table 11) [11].…”
Section: The Intramolecular Oxa-michael Addition Of Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Various catalysts have been reported for intermolecular oxa-Michael additions, such as pro-azaphosphatranes of ionic liquid as solvent for toluenesulfonic acid-catalyzed oxa-Michael addition has also been reported. 22 For intramolecular oxa-Michael addition, cinchona alkaloids, 23 thiourea derivatives, 24 quinine, 25 guanidine, 26 30,31 have been utilized as the catalysts. It was reported that the intramolecular oxa-Michael addition of (E)-1-aryl-4-hydroxy-4-methylpent-1-en-3-ones in the presence of TsOH should be carried out by refluxing in dichloroethane for 24 h, while the products were hard to purify due to the impurities.…”
Section: Introductionmentioning
confidence: 99%